2022
DOI: 10.3390/pathogens11060699
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Meningitis in Kidney Transplant Recipients: A Two-Decade Cohort Study in France

Abstract: Cryptococcosis is the third most common cause of invasive fungal infection in solid organ transplant recipients and cryptococcal meningitis (CM) its main clinical presentation. CM outcomes, as well as its clinical features and radiological characteristics, have not yet been considered on a large scale in the context of kidney transplantation (KT). We performed a nationwide retrospective study of adult patients diagnosed with cryptococcosis after KT between 2002 and 2020 across 30 clinical centers in France. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In a multicenter study of cryptococcal infections, 54% were identified as having pulmonary infections, 52.2% had CNS involvement, and 8.1% had skin/soft tissue/osteoarticular infections [ 107 ]. In a study of kidney transplant patients, presenting symptoms in cases of cryptococcal meningitis were headache, focal neurological signs, fever, and vomiting [ 109 ]. Cryptococcal pneumonia typically radiographically presents as solitary or multiple nodules.…”
Section: Cryptococcusmentioning
confidence: 99%
“…In a multicenter study of cryptococcal infections, 54% were identified as having pulmonary infections, 52.2% had CNS involvement, and 8.1% had skin/soft tissue/osteoarticular infections [ 107 ]. In a study of kidney transplant patients, presenting symptoms in cases of cryptococcal meningitis were headache, focal neurological signs, fever, and vomiting [ 109 ]. Cryptococcal pneumonia typically radiographically presents as solitary or multiple nodules.…”
Section: Cryptococcusmentioning
confidence: 99%
“…In HIV/AIDS, infection typically manifests with CD4 T-lymphocyte counts under 100 cells/µL [26]. Other risk factors for cryptococcal disease include solid organ transplant [27], calcineurin inhibitors and other immunomodulatory agents [28], auto-antibodies against granulocyte-macrophage-colony stimulating factor (anti-GM-CSF) [29], decompensated cirrhosis [28], type 2 diabetes mellitus, malignant solid tumours, autoimmune diseases and chronic kidney disease [30]. Pulmonary disease in all these contexts is common although dissemination has been reported to be associated with pre-existing renal impairment [31].…”
Section: Epidemiology and Host Risk Factorsmentioning
confidence: 99%
“…As an opportunistic pathogen, C. neoformans primarily affects those who are immunocompromised due to conditions such as acquired immunodeficiency syndrome, organ transplantation on immunosuppressive agents, or malignancy on anti-cancer drugs [ 1 , 3 ]. Specifically, among solid organ transplant recipients who contracted invasive fungal infections, cryptococcal infection occurred in approximately 8% of the patients, with most cases occurring after 12 months following transplantation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The central nervous system (CNS) is the most common site of disseminated infection; however, the skin and soft tissue, eyes, bones, prostate, and lymph nodes may all be involved as well. In kidney transplant patients with cryptococcal meningitis, diagnostic delays occur due to non-specific symptoms, and the mortality rate can be as high as 40% at 12 months [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%